Geometry and stratigraphy of the Limeira tholeiitic intrusion, Paraná¡ magmatic province (SP-Brazil) - Santos, Lucas Martins A. dos (2018)
The Limeira Intrusion is an occurrence related to the Mesozoic continental flood basalts of Paraná Magmatic Province, cropping out at the eastern São Paulo state. It is made up of basic- intermediate rocks with a great diversity of structures, textures, and modal compositions, related to the specific evolutionary process in a magma chamber. 2D forward modeling of magnetometric data, based on available aerial and newly obtained ground data integrated with in situ rock magnetic susceptibility measurements, were used to establish its geometry. The results, even considering intrinsic drawbacks of magnetometric theoretical models, are compatible with the geologic-based presumed intrusion geometry. In addition, the stratigraphic analysis of compositional and textural variations, coupled with the structural and geometric features, allowed the interpretation of its emplacement mechanism and thermal evolution. Quantitative textural analysis through crystal size distribution (CSD) of plagioclase crystals, the spatial distribution pattern of structures, microtextures, granulation, and rock-types, evidenced the internal heterogeneities of this occurrence. An approximately 110 m top-to-floor exposure section reveals that its internal heterogeneity was caused by non-instantaneous successive emplacement of three different magma injections. The textural analysis also reveals fine-grained crystals formed under different cooling paths, present in medium- to coarse- grained rocks within the intrusion, next to sharp contacts between different rock compositions. The contacts between different rocks are characterized by hybridization textures and by significant amounts of plumose granophyre-type and plumose plagioclase. The time lapse between consecutive pulses is responsible for a stepwise cooling-path, preservation of hybridization textures, and the development of almost rigid surfaces providing crystals alignment during magma flow. High-resolution Sr-isotopy data demonstrates a complex assembly history, possibly involving filter pressing of residual liquids, and pre-existent crystals before magma installation in coarse-grained rocks. It is also possible to recognize fewer amounts of country-rocks assimilation, which decreases towards the intrusion\'s core and can be associated with magma migration due to filter pressing processes. In the feeder zone, the evolution of emplacement was marked by an almost continuous decrease in wall-rock assimilation by the consecutive magma batches.